Color from within: A new vector in the studies of urban coloristics - Griber, Yulia (project baikal, 2022)
The most important feature of modern studies of urban coloristics is a special vector of viewing: not “from above”, but “from within”, “from a close distance”, from the perspective of a citizen. This principle completely changes the usual research practice and requires special tools that can capture how citizens actually see urban colors, how they feel, how they remember and use peculiarities of the color environment.
Keywords: color; urban environment; coloristics; architecture; urban planning; design